THE EFFECT OF COMPUTER ASSISTED LANGUAGE LEARNING AND STUDENTS’ LEARNING MOTIVATION TOWARD STUDENTS’ GRAMMAR MASTERY OF THE FIRST YEAR STUDENTS AT AMIK SELATPANJANG KABUPATEN KEPULAUAN MERANTI - MASHUDI MASHUDI (INOVISH JOURNAL, 2018)
In learning grammar, appropriate teaching strategy and great motivation can enhance students’ grammar mastery. CALL stratey was used as the variation ofteaching and learning toward grammar mastery. The goal of this research was to find out the effect of CALLstrategy and learning motivation toward students’ grammar mastery. The design of this research wasquasi experimental research. The population of this research was the students of first year in academic 2016/2017 at AMIK Selatpanjang Kabupaten Kepulauan Meranti. The techniqueused in selecting the sample was Cluster Random Sampling. The sample of this research was A1 as the experimental class and B1 as the control class. The instrumentsused in this research were grammar mastery test and questionnaire test. The hypotheses were analyzed by using t-test and Two Ways ANOVA.  The finding showed that (1) Students taught by using CALL strategy produced better achivementtoward students’grammar masteryas compared to CLT strategy.(2) Students with high learning motivation taught by using CALL strategy produced better achievement toward grammar mastery than high motivated learning students taught by using CLT strategy. (3) Students with low learning motivation taught by using CALL strategy produced lower achievement toward grammar mastery than low motivated learning students taught by using CLT strategy. (4) There was nointeraction between teaching strategies (CALL and CTL) and students’ learning motivation toward grammar mastery. In conclusion, CALL strategy worked effectively to produce better achievement as the teaching and learning strategy toward grammar mastery at AMIK Selatpanjang Kabupaten Kepulauan Meranti.